The Role of Green Infrastructure in Answering Distributional Questions. - Gantioler, Sonja (Lit, 2020)
According to its EU definition, the term green infrastructure (GI) refers to the conservation and restoration of a network of natural and semi-natural areas, environmental features and open spaces that contribute to the conservation of biological diversity and/or are responsible for providing a range of functions and benefits for human well-being. More importantly, GI has been brought forward as a method that - via conserving, restoring and connecting remaining patches at different scales - can ensure a wider availability and access to green spaces and their benefits and as such increase the proportion of the public benefitting from it and contribute to equity in the wealth it provides. What the concept green infrastructure actually means in practice is still largely the subject of on-going discussions and negotiations between researchers and practitioners, including different disciplines from ecology, environmental engineering, landscape architects and economics. It needs to be emphasized that there is no common agreement on the term's definition - the origins of its principles are various and they are often interpreted differently, depending on the context and geographical area in which they are used. The first step of the ongoing thesis was to look into what movements, initiatives and concepts the term historically builds on and what the main drivers of implementation have been. The aim was to gain a better understanding of the various interpretations of GI principles and characteristics and to examine to what extent they differ from its predecessor.
Keywords: Stadtgrün; Freiraumnutzung; Infrastrukturversorgung; Stadtökologie; Grünraumplanung; Umweltgerechtigkeit; Wohlbefinden; Grüne Infrastruktur